SCIENTIFIC AND PRACTICAL PROBLEMS OF IMPLEMENTATION OF THE PROVISIONS OF THE COUNCIL OF EUROPE CONVENTION ON PREVENTING AND COMBATING VIOLENCE AGAINST WOMEN AND DOMESTIC VIOLENCE IN THE NATIONAL LEGISLATION OF UKRAINE - Levchenko, Kateryna; Legenkyi, Mykola; Legenka, Marina; Dunebabina, Olha (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article substantiates the socio-political significance of Ukraine’s ratification of the Council of Europe Convention on preventing and combating violence against women and domestic violence and the relevance of legal scientific developments to determine the best ways to implement the provisions of this regulatory document. Research methods: in accordance with the purpose of the study, during the work on the article, such general scientific methods as the hypothetical-deductive method, analysis and induction were used. In addition, special methods were also applied, first of all – theoretical and legal and specially-legal, which provided coverage of the situation regarding the ratification of this international legal document through a political and legal prism and with the use of legal terminology. The method of integrative cognition analyzed the dialectic of normative-legal and organizational support for combating violence against women and domestic violence in the works of foreign and Ukrainian scientists. The results: legal studies on the introduction of the convention in different European countries are summarized. It is pointed out the complications that have arisen and determined perspective methods that can be used in Ukraine. The studies of Ukrainian legal scholars on the relevance of the implementation of the convention norms in Ukraine, taking into account the existing peculiarities of social relations, are analyzed. The historiographical aspects that preceded the implementation of the Convention in Ukraine are studied, the stages and main achievements of this work are investigated, changes in the legal field made to achieve this goal are determined. Attention was drawn to the need to carry out scientific research on the extraterritoriality of the Convention and to resolve issues related to the expansion of Ukraine’s jurisdictions to situations of violence against Ukrainian citizens abroad, which is especially important in the situation of forced migration of women and children from Ukraine. The need to bring the national practice of combating all forms of violence in line with the standards of the Istanbul Convention on the Protection of Victims of Violence, Punishment of Offenders, Proper Prevention and Coordination, taking into account modern social challenges and the continuation of the Russian Federation’s large-scale war against Ukraine, is substantiated. The main ways of implementing the Convention are monitoring the current legislation and improving it in view of compliance with the standards of the Convention, expanding the practices of protecting victims and punishing offenders, increasing attention to preventing and combating violence against children, strengthening cooperation with countries where Ukrainian internally displaced persons are staying in order to combat violence, updating training programs for relevant specialists and deploying relevant information campaign.